Pemanfaatan Penanaman Cemara Udang sebagai Strategi Revitalisasi Kawasan Pantai dalam Rangka Optimalisasi Ekowisata Berkelanjutan - Esti Utarti; Rendy Setiawan; Susantin Fajariyah; Mashuri Mashuri; Shafa Nashrullah; Tasya Preira Farrennina; Syafira Lailatul Ulfa Marfuah (Forum Kerjasama Pendidikan Tinggi, 2026)
Pancer Coastal is one of the southern sea beaches located in Puger Kulon Village, Jember. The characteristics of the beach and the sloping geographical allow Puger Kulon Village to develop into a beach-based tourism village. The southern sea has a harsh choppy character with sandy beaches so it needs plant vegetation that acts as a barrier. The need for vegetation as a barrier in the second zone besides the sea pandan which already exists as the first barrier initiated the planting of shrimp cypress in the Pancer coastal area. Planting shrimp cypress is beneficial in resisting wind speed and keeping air conditions cooler in addition to being able to reduce the impact of tsunamis and abrasion in coastal areas. Shrimp cypress can live in extreme conditions, resistant to drought and strong gusts of wind and pest attacks. This activity aims to revitalize the pancer beach area in order to support sustainable ecotourism. This activity is carried out through observation, coordination with related parties, provision and planting of shrimp cypress seedlings, shrimp cypress maintenance and provision of coastal environmental management modules. A total of 200 shrimp cypress seedlings have been planted on Pancer coastal involving the assisted village service team in collaboration with the village government, Pokdarwis and marine members from the Pam Puter XXVIII Nusa Barong Island Ops Task Force.